Effect of taurine supplementation on fat and energy absorption in cystic fibrosis. Issue 9 (September 1992) - De Curtis, M; Santamaria, F; Ercolini, P; Vittoria, L; De Ritis, G; Garofalo, V; Ciccimarra, F
Abstract : In 10 children with cystic fibrosis and persisting steatorrhoea, supplementation with taurine (30-40 mg/kg/day) was given for two months as an adjunct to the usual pancreatic enzyme treatment. A three day fat and energy balance was performed in patients with cystic fibrosis, before and after the supplementation, and in seven healthy controls who did not receive taurine. Faecal fat was measured by a gravimetric method and stool energy was determined using a bomb calorimeter. Patients with cystic fibrosis, before and after taurine, and healthy controls received the same fat and energy intake (calculated by a dietitian). In patients with cystic fibrosis taurine did not produce any improvement of steatorrhoea (mean (SD) faecal fat 8.7 (3.3) v 11.2 (7.0) g/day, respectively before and after the supplementation), of faecal energy loss (0.978 (0.468) v 1.133 (0.539) MJ/day), of faecal fat expressed as percent of fat intake (13.4 (5.6) v 15.1 (9.8)%), and of faecal energy expressed as percent of energy intake (9.9 (3.6) v 11.2 (5.7)%). Healthy controls had significant lower fat (3.5 (2.3) g/day) and energy 0.576 (0.355) MJ/day faecal losses. In conclusion, taurine failed to decrease significantly fat and energy losses. Our study does not support the use of taurine supplementation in the nutritional management of cystic fibrosis.